Reliability of Body Landmark Analyzer (BLA) System for measuring hyperkyphosis and hyperlordosis abnormalities - Yousefi, M.; Ilbiegi, S.; Naghibi, S. E.; Farjad Pezeshk, S. A.; Zanguee, H. (Journal of Advanced Sport Technology, 2020)
Among the several postural alterations, the thoracic hyperkyphosis and lumbar hyperlordosis are the most common ones. Hyperkyphosis is defined as an outward curvature of the thoracic spine and hyperlordosis is defined as an inward curvature of the lumbar. There are many methods as invasive and non- invasive for calculating of spinal column abnormalities. The purpose of the present research was to study the reliability of the Body Landmark Analyzer (BLA) method for measuring of the thoracic kyphosis and lumbar lordosis curvatures of the spinal column. Seventeen healthy males participated in this study. Intra-class correlation coefficient (ICC) two-way mixed model on absolute agreement was used to identify the inter/intra raters` reliability and 95% confidence intervals. Considering the results of this research indicated high Intra-class correlation coefficients for the thoracic kyphosis and lumbar lordosis 0.87- 0.90 and 0.84- 0.88 respectively, therefore it can emphasized that BLA method has succeeded to make a high reliability for both of the thoracic kyphosis and lumbar lordosis curvatures of the spinal column. Based on the mentioned capabilities and reliability of this method, it can suggest along with other non-invasive methods for diagnosing of kyphosis and lordosis abnormalities.